Contemporary Principles of Heterodox Political Economy (In Russian Language) - O'Hara, Phillip (Rossiiskaia Akademiia Nauk, 2009)
This paper elaborates on the major principles of heterodox political economy, drawing on converging trends in the major schools. These schools include neo-Marxian, Veblenian, post-Keynesian, feminist, social, ecological and international political economy. These schools have been cooperating in the development of an intellectual and policy-relevant set of conceptual insights into the workings of capitalism and alternative perspectives on future political-economic systems. There are five dominant principles emerging out of this cooperative venture between the major schools. The first principle is historical specificity, attempting to situate political-economic processes in a historical and cultural space. The second is circular and cumulative causation, linking the dominant variables in holistic interdependency. The third is contradictory processes operating between society and economy, industry and finance, capital and labor, and world economy and national economy. The fourth principle is heterogeneous agents, where individuals are influenced by their multiple group positions affected by class, gender, ethnicity, species and nationality. The fifth principle is uneven development, where uneven processes operate in the world and regional economy. Some policy implications of these principles are also examined.